2020
DOI: 10.1177/2058738420907188
|View full text |Cite
|
Sign up to set email alerts
|

Shrimp sensitization in house dust mite allergic patients

Abstract: Shrimp tropomyosin has a similar structure to house dust mite (HDM) tropomyosin. In this research, 232 adult patients with symptoms of persistent allergic rhinitis were randomly selected. In the group, 59% were sensitized to Dermatophagoides pteronyssinus and 57.8% to Dermatophagoides farinae. In total, 128 (55.2%) patients were sensitized to both HDM species and 143 (61.6%) to at least one. Slightly over a quarter (25.4%) of patients were sensitized to shrimp. Of the 35 shrimp-sensitized patients, the sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…As observed in our previous study, there was high concordance of sIgE against Der p 10 and Pen m 1 (ImmunoCap) (Spearman correlation 0.918, p < 0.001), which may indicate that it is economically sensible to diagnose shrimp allergy using only one of the methods. 25 We also found positive correlations between concentrations of sIgE to Der p 1, Der p 2 and Der p 10 by singleplex ImmunoCap and the corresponding allergen components in ImmunoCap ISAC. Not all patients with elevated sIgE according to the singleplex ImmunoCap method were detected, but the detection rate was above 84% in both cases.…”
Section: Discussionsupporting
confidence: 61%
“…As observed in our previous study, there was high concordance of sIgE against Der p 10 and Pen m 1 (ImmunoCap) (Spearman correlation 0.918, p < 0.001), which may indicate that it is economically sensible to diagnose shrimp allergy using only one of the methods. 25 We also found positive correlations between concentrations of sIgE to Der p 1, Der p 2 and Der p 10 by singleplex ImmunoCap and the corresponding allergen components in ImmunoCap ISAC. Not all patients with elevated sIgE according to the singleplex ImmunoCap method were detected, but the detection rate was above 84% in both cases.…”
Section: Discussionsupporting
confidence: 61%
“…In our previous studies based on the assessment of the concentrations of sIgE Der p 10 and Pen a 1 in the quantitative ImmunoCap method, the correlation coefficient between these concentrations was as much as 0.987. This suggested that it was economically unjustified to use both determinations, as the results practically coincided [19]. In the present study, the use of the semiquantitative ImmunoCap ISAC method, characterized by lower sensitivity, resulted in a significantly greater discrepancy between results.…”
Section: Discussionmentioning
confidence: 50%
“…In that study population, 86 (90.5%) patients had positive skin prick tests for house dust mite allergens [18]. As our previous observations indicated, among 232 patients with symptoms of allergic rhinitis and as many as 59 patients had elevated levels of shrimp sIgE, while only 12 were not allergic to house dust mites (20.3%) [19]. The differences may be due to a different population selection criterion, however, the high frequency of mite allergy in patients allergic to shrimp allergens is confirmed.…”
Section: Discussionmentioning
confidence: 51%
“…Our study is the first to describe molecular sensitization patterns to HDM allergens in a Lithuanian population and to highlight the role played by age and gender, while simultaneously analyzing the phenomenon of concomitant reactivity among different allergens. [18][19][20] Immediate hypersensitivity to indoor allergens increases the risk of asthma, allergic rhinitis, and atopic dermatitis. HDM sensitization is globally recognized as the leading cause of inhaled allergen-triggered allergies.…”
Section: Discussionmentioning
confidence: 99%